Migrants as Visitors: A Colour-Blind Approach and Imagined Racial Hierarchy - Raúl, Nicola; Šotola, Jaroslav (Lidé města, 2018)
This article provides the results on research into the attitudes of Czech seniors towards foreigners of non-European origin. It is based on an interpretation of ten semi-structured interviews of a biographical nature, focused on the participants’ encounters with otherness. Regardless of the political regime and the period of time, the main feature of this contact is distance and separation from foreigners. From the point of view of seniors, migration is an unnatural and only temporary phenomenon that has to be controlled and restricted by the state. Negative attitudes towards foreigners in the narrations are concealed by seemingly neutral statements that are subject to an effort of not providing any reason for being labelled as a “racist”. Nevertheless, it is still possible to uncover the idea of self-evident power superiority over categories of people understood as racially different. Although the seniors expressed various levels of sympathy, indifference, or antipathy towards the individual non-European groups, we believe that these differences are not a manifestation of selective acceptance, but rather a manifestation of imagined racial hierarchy in which groups perceived as submissive are preferred.